Study on viscoelasticity and damping properties of OSA/PAAM hydrogel - Zhang, Xiaoran; Zhang, Xin; Wang, Puying; Wang, Xinze; Zhong, Linlin; Ma, Songmei; Xu, Wenlong (Journal of polymer research, 2024)
The problems of vibration and noise have seriously affected people’s production and life. Hydrogel can be used as damping material because of its good viscoelasticity, but the current damping material is difficult to meet the needs of actual production and life because of the lack of wide damping temperature and frequency range and high loss factor. In this work, ammonium persulfate was used as both initiator and oxidant to form a mixed double network hydrogel of polyacrylamide and oxidized sodium alginate. The double network hydrogel prepared by this method has good adhesion and mechanical properties. In addition, due to the adjustable viscoelasticity of the hydrogel, the hydrogel shows excellent damping properties. When the concentration of MBA is 0.02%, it can reach the temperature range of 0-125 ℃, and the damping factor is more than 0.3. The visualization experiment proves the practical application effect of the hydrogel, so it is expected to be used as a damping material in damping, noise reduction and other fields in the future.